Prescribing pattern of antimicrobial agents in the pediatric intensive care unit of a tertiary care teaching hospital in puducherry union territory. - J. PANDIAMUNIAN; ANNABELLE RAJASEHARAN; KARTIK J SALWE; BHANU PRAKASH KOLASANI (International Journal of Pharma and Bio Sciences, 2017)
This study was done to evaluate the prescribing pattern of antimicrobial agents (AMA) in the NICU of a tertiary care teaching hospital. A prospective, hospital-based, cross-sectional prescription audit was conducted with 100 case records of children admitted in the PICU of a tertiary care teaching hospital located in Puducherry Union Territory. Cefixime (25.2%) and Ampicillin (23.8%) were found to be the most frequently prescribed antimicrobial agents. Penicillins (41.72%) and Cephalosporins (34.43%) were the most frequently prescribed groups of AMAs in the studied PICU. Majority (66.66%) of antimicrobial prescriptions were made for non-bacteriologically proven infections. CSF specimens were taken for culture in 4 cases out of 100 patients to identify pathogenic organisms and no specimen showed positive culture. Our data shows more frequent use of betalactam antibiotics in the PICU and most AMA prescriptions were made without supporting bacteriological evidence in the PICU.